Women, rites, and ritual objects in premodern Japan - Gerhart, Karen M. (Brill's Japanese studies library, 2018)
"Women, Rites, and Ritual Objects in Premodern Japan, edited by Karen M. Gerhart, is a multidisciplinary examination of rituals featuring women, in which significant attention is paid to objects produced for and utilized in these rites as a lens through which larger cultural concerns, such as gender politics, the female body, class, and materiality, and the importance of objects as active participant in rituals, are explored. The ten chapters encounter women, rites, and ritual objects in many new and interactive ways and constitute a pioneering attempt to combine ritual and gendered analysis with the study of objects"--